Material and Spiritual Poverty: A Postmodern Psychological Perspective on a Perennial Problem - Helminiak, Daniel A. (Journal of religion and health, 2020)
From a social-scientific perspective, this paper addresses an overlooked dimension of material poverty, namely spiritual poverty or the lack of spiritual sensitivity, and calls it a psychological disorder. Religions link deep spirituality with a kind of "poverty," namely simplicity of lifestyle and generosity toward the needy; but none advocates the poverty of outright destitution. A fully psychological "spiritualogy" - built on Bernard Lonergan’s analysis of human consciousness or spirit and consonant with the humanistic psychology of Carl Rogers and Abraham Maslow and current psychotherapeutic understanding - explains the link between spirituality and poverty as a matter of personal integration and suggests interventions to address the corrosive epidemic soul sickness of the postmodern world, so different from traditional societies in which religion and culture intertwined and functioned effectively.